Methane Emissions from Paddy Rice Fields: Strategies towards Achieving A Win-Win Sustainability Scenario between Rice Production and Methane Emission Reduction - Epule, Epule Terence; Peng, Changhui; Mafany, Ndiva Mongoh (Journal of Sustainable Development, 2011)

Rainfall and Deforestation Dilemma for Cereal Production in the Sudano-Sahel of Cameroon - Epule, Terence Epule; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Journal of Agricultural Science, 2012)

Forest Loss Triggers in Cameroon: A Quantitative Assessment Using Multiple Linear Regression Approach - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Journal of Geography and Geology, 2011)

Enabling Conditions for Successful Greening of Public Spaces: The Case of Touroua, Cameroon Based on Perceptions - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Small-scale Forestry, 2014)

The causes, effects and challenges of Sahelian droughts: a critical review - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Regional Environmental Change, 2014)

Policy options towards deforestation reduction in Cameroon: An analysis based on a systematic approach - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Land Use Policy, 2014)

Well Water Quality and Public Health Implications: the Case of Four Neighbourhoods of the City of Douala Cameroon - Epule, Terence Epule; Peng, Changhui; Mirielle Wase, Moto; Mafany, Ndiva Mongoh (Global Journal of Health Science, 2011)

An assessment of the predictors of the dynamics in arable production per capita index, arable production and permanent cropland and forest area based on structural equation models - Epule, Epule Terence; Bryant, Christopher Robin; Akkari, Cherine; Sarr, Mamadou Adama; Peng, Changhui (SpringerPlus, 2014)

Model prediction of biome‐specific global soil respiration from 1960 to 2012 - Zhao, Zhengyong; Peng, Changhui; Yang, Qi; Meng, Fan‐Rui; Song, Xinzhang; Chen, Shutao; Epule, Terence Epule; Li, Peng; Zhu, Qiuan (Earth's Future, 2017)
Abstract Biome‐specific soil respiration (Rs) has important yet different roles in both the carbon cycle and climate change from regional to global scales. To date, no comparable studies related to global biome‐specific Rs have been conducted applying comprehensive global Rs databases. The goal of this study was to develop artificial neural network ( ANN ) models capable of spatially estimating global Rs and to evaluate the effects of interannual climate variations on 10 major biomes. We used 1976 annual Rs field records extracted from global Rs literature to train and test the ANN models. We determined that the best ANN model for predicting biome‐specific global annual Rs was the one that applied mean annual temperature ( MAT ), mean annual precipitation ( MAP ), and biome type as inputs ( r 2 = 0.60). The ANN models reported an average global Rs of 93.3 ± 6.1 Pg C yr −1 from 1960 to 2012 and an increasing trend in average global annual Rs of 0.04 Pg C yr −1 . Estimated annual Rs increased with increases in MAT and MAP in cropland, boreal forest, grassland, shrubland, and wetland biomes. Additionally, estimated annual Rs decreased with increases in MAT and increased with increases in MAP in desert and tundra biomes, and only significantly decreased with increases in MAT ( r 2 = 0.87) in the savannah biome. The developed biome‐specific global Rs database for global land and soil carbon models will aid in understanding the mechanisms underlying variations in soil carbon dynamics and in quantifying uncertainty in the global soil carbon cycle. , Key Points Predict biome‐specific global soil respiration from 1960 to 2012 using an artificial neural network model Prediction determined an average global soil respiration of 93.3 ± 6.1 Pg C yr −1 and an increasing trend of 0.04 Pg C yr −1 The 10 biome‐specific soil respiration estimates made it possible to trace different responses to global climate change in each biome